'Bank systemic risk: An analysis of the sovereign rating ceiling policy and rating downgrades - Md Abdul, Wasi; Pham, Thu Phuong; Ralf, Zurbruegg (Wiley-Blackwell, 2022)
We investigate the impact that the sovereign ceiling policy has on financial stability. In the event of a sovereign rating downgrade, we find that the rating agencies' sovereign ceiling policy leads to a disproportionate downgrade of the most creditworthy financial institutions in the economy and results in increased systemic risk. This asymmetric variation in bank ratings also impairs equity growth that further exacerbates bank insolvency. Our results are robust to several matching techniques, such as propensity score matching and entropy balancing, falsification tests, subsample analyses, alternative empirical proxies and model specifications.